2017
DOI: 10.1016/j.nicl.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of mild cognitive impairment and Alzheimer's disease using structural MRI cortical thickness, hippocampal shape, hippocampal texture, and volumetry

Abstract: This paper presents a brain T1-weighted structural magnetic resonance imaging (MRI) biomarker that combines several individual MRI biomarkers (cortical thickness measurements, volumetric measurements, hippocampal shape, and hippocampal texture). The method was developed, trained, and evaluated using two publicly available reference datasets: a standardized dataset from the Alzheimer's Disease Neuroimaging Initiative (ADNI) and the imaging arm of the Australian Imaging Biomarkers and Lifestyle flagship study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(107 citation statements)
references
References 57 publications
(100 reference statements)
7
91
0
Order By: Relevance
“…Interestingly, HVLT-R total recall and NACC delayed recall for a passage were uniquely related to decreased CoTH in the superior parietal regions. There is increasing recognition that volumetric measures may differ from measures of CoTH in relationship to cognitive processes [24, 25], and our findings indicate that this is an area worthy of further research.…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, HVLT-R total recall and NACC delayed recall for a passage were uniquely related to decreased CoTH in the superior parietal regions. There is increasing recognition that volumetric measures may differ from measures of CoTH in relationship to cognitive processes [24, 25], and our findings indicate that this is an area worthy of further research.…”
Section: Discussionmentioning
confidence: 72%
“…25 Another study reported 62.7% accuracy in classification of CU, MCI, and AD using anatomical features that included hippocampal shape, texture, and cortical thickness. 29 A whole-brain hierarchical network analysis of >700 brain images showed accuracy of CU vs. MCI: 84%; CU vs. AD: 94%; MCI vs.…”
Section: Discussionmentioning
confidence: 99%
“…Texture analysis is a statistical method of quantifying gray‐level intensity and patterns in an image that the human eye cannot detect. Studies have applied texture analysis in conventional MR images to characterize and diagnose various neurological diseases including brain tumors and Alzheimer's disease (Kickingereder et al, ; Sørensen et al, ). A novel three‐dimensional (3D) voxel‐wise texture analysis method also revealed the spatial pattern of pathology involving the medial temporal lobes in Alzheimer's disease in a hypothesis‐free study (Maani, Yang, & Kalra, ).…”
Section: Introductionmentioning
confidence: 99%